Unused and Expired Medications: Are They a Threat? A Facility-Based Cross-Sectional Study - Awol Jemal Ebrahim; Fitsum Sebsibe Teni; Dawit Kumilachew Yimenu (SAGE Publishing, 2019)
Background: A significant amount of potentially effective and lifesaving medications were wasted at the health facilities due to lack of a system for checking their effectiveness and returning them to the system. Objectives: To assess the prevalence of unused medications and related consequences in selected health facilities of Awi zone, Amhara regional state, Ethiopia. Methods: A facility-based cross-sectional study design supplemented by a qualitative approach was employed. Descriptive data were collected using checklists while interviews were conducted with respective personnel at the health facilities. Results: A total of 4 health facilities were included in the study. During the 1 month of study period, 56 types of medications were found unused at the health facilities. Anti-infective medications were the most commonly unused medications 36.4%. At the in-patient departments of the 4 hospitals, a total of 173 medications were found unused. Similarly, 605 medications were found wasted at the pharmacy stores of those hospitals in the 2009 fiscal year. Conclusion: A significant amount of unused medications were present at the health facilities. Health facilities need to monitor health professionals strictly follow national and international treatment guidelines and monitor the rational use of medications.